(untitled) (Journal of Medical & Health Sciences Review, 2025)
Malakand Wildlife Safari Park is situated in District Malakand, approximately 110 km from Peshawar and 230 km from Islamabad. This research study was conducted on fauna of Malakand safari park. This park is enclosed area of 240 acres and was established by Khyber Pakhtunkhwa wildlife department. The goal of our study was to evaluate the fauna of the park. For the collection of data, we used the personal interviews method and acquiring it by visiting there by ourselves, watching and noticing their movements. There are four major mammal’s species present in wildlife safari park including leopards, grey goral, rhesus monkeys, and in birds there is a pleasantry site which accommodate 15 different type of species which total count of 91 birds, 35 of them are male while the rest 56 are female. The peasantry occupies 2340 square feet of land with 20 fenced cages. The total number of animals is 102. There is a kalij breeding center which facilitate the artificial breeding of kalij pheasants. The park is well fenced to protect these species. Issues of the park contains accessibility of roads to the park, eucalyptus plantation is also an issue which affected the indigenous plants and water problem.